Anteseden Kepuasan Dan Loyalitas Nasabah Berbasis Kualitas Layanan Dan Religiusitas Pt Bpr Syariah Bangun Drajat Warga Di Yogyakarta - Wijayanta, Yuda Anggara (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Technological developments are so fast and will continue to grow, not least in the banking industry. Commercial banks will be more flexible in following technological developments with large capital as a support. However, for people's financing banks that have small capital, many still rely on conventional methods. This study aims to determine the effect of service quality and religiosity on customer satisfaction and customer loyalty. The population in this study are active financing customers at PT BPR Syariah Bangun Drajat Warga, Yogyakarta. The research results were analyzed by Anova test using R Studio software. The results of this study are 1) Service quality significantly affects customer satisfaction with a significance value of 2.2e-16, 2) Religiosity significantly influences customer satisfaction with a significance value of 5.986e-14, 3) Service quality significantly influences customer loyalty with a significance value 3.653e-9, 4) Religiosity significantly affects customer loyalty with a significance value of 3.121e-6, and 5) customer satisfaction significantly affects customer loyalty with a significance value of 1.375e-10.